The Saudi Arabian Women Military Existence in the Islamic Perspective - Afni Regita Cahyani Muis; Usep Abdul Matin (Buletin Al-Turas, 2022)
Purpose                  The purpose of this research was to explain in depth about the role of women army into Saudi Arabia’s military institutions in Mohammad Bin Salman regime. Method                   The study was a qualitative research with descriptive design using a primary data that were the journalists’ and academicians’ opinion or ideas. It used interviews with a researcher for the Center for Islamic and Occidental Studies, University of Darussalam Gontor, and with the journalist and academician from King Saud University. The study also depended on the secondary data literatures review like book, journal, and official website. The data then were analyzed qualitatively using the Islamic perspective of the women role in life.  Results/FindingsAs a state which originally tightened the rules for women in the public sphere, the existence of women military in Saudi Arabia was a certain reformist. The engagement of woman military into the state affairs has contributed to Arab Saudi’s security stability that becomes the heart of Middle East as the most frequently visited by foreign people. It has a positive approach for improving the security system of Saudi Arabia as a global image builder. ConclusionThe urgency of women military in Saudi Arabia is to answer the public needs and service. Women Military in Saudi Arabia become a non-combatant for manifestation of the Kingdom of Saudi Arabia's vision to provide an opportunity for women into the public sphere. The Saudi Arabia's women military still maintains sharia principles as a political instrument.